PERBANDINGAN KUAT TEKAN BETON DENGAN MENGGUNAKAN ALAT UJI TEKAN DAN PALU BETON - Amir, Mardiana; Kombong, Wenys; Idris, Muhammad (FORUM BANGUNAN, 2013)
Testing method using a laboratory test machine press basically gives an accurate value for the specimen made up destroyed. While the test method test hammer (hammer concrete) made with infact burden (impact) on the surface of the concrete by using a mass that is activated by using a certain amount of energy in concrete construction, for example on the beam. The purpose of this study was to determine differences in the average compressive strength of the resulting test press until crushed (using a pressure test) and a test based infact press (using a hammer concrete). To test the field Test Hammer made of reinforced concrete beams (15cmx20cm x 200cm) made 1 piece samples (tested the left side, right and center. Subsequently the specimen was care for 27 days and testing of compressive strength at 28 days. Directions vertical concrete test hammer down α = - 90. Based on test results obtained in this study: average compressive strength - flat with a hammer and a concrete cylinder specimen gives the smallest value is: 263.7 kg/cm2. Compressive  average using Hammer Concrete and concrete beam specimen gives a higher value, namely: 288.5 kg/cm2.Compressive press average using engine compression test gives the highest value, 300.9 kg/cm2. Average ratio between using compressive strength machine  and  using test tools hammer concrete: 1.043 (beam specimen) and 1, 141 (cylindrical specimen).